Perancangan Antena Metamaterial Patch Circular Untuk Teknologi 5G Dengan CSRR Pada Frekuensi 3.5 GHz - Tri Cahyani, Kenita; Olivia Nur, Levy; Hian Ryanu, Harfan (ALINIER: Journal of Artificial Intelligence & Applications, 2023)
The development of 5G technology at this time has a much faster speed, capacity and latency in accessing data compared to 4G technology. 5G technology has several components that are influential in the application of 5G technology, one of which is the antenna. Microstrip antennas are antennas that have simple materials, smaller antenna dimensions, so that production costs are cheaper, affordable and the performance of microstrip antennas is quite good. Microstrip antenna has several drawbacks, namely low gain and not wide bandwidth. In this study a circular patch microstrip antenna was designed using FR-4 material using a relative dielectric constant of 4.4, a loss tangent of 0.02 and a substrate thickness of 1.6 mm. The microstrip antenna that will be added to the groundplane section uses a metamaterial structure, namely the Complementary Split-Ring Resonator (CSRR) which operates at a frequency of 3.5 GHz. The addition of the CSRR metamaterial structure aims to increase antenna bandwidth and miniaturization. The simulation results of a microstrip antenna without CSRR can work at a frequency of 3.5 GHz with a return loss of -15.71 dB, a VSWR of 1.39, a gain of 2.121 dBi, a bandwidth of 120 MHz and the resulting radiation pattern is unidirectional. While the antenna that has been added CSRR at a frequency of 3.5 GHz has a return loss of -19.50 dB, a VSWR of 1.23, a gain of 1.454 dBi, a bandwidth of 410 MHz, the resulting radiation pattern is bidirectional and the antenna undergoes miniaturization at a groundplane width of 18%. That way the antenna using the CSRR method can increase bandwidth and miniaturization.